Prom kings - Correia, Tony (RealLove., 2019)
"When the queer prom committee asks Charlie to join them, Charlie figures it'll be a good way to get closer to cute new guy Andre - and maybe even ask him to be his prom date! The only problem is that Charlie has competition for Andre's attention in rich, good-looking Chad, who Charlie can't stand. Charlie and his pal Luis come up with a plan to get Andre's attention - to woo Andre as a secret admirer and then reveal Charlie's true identity with a spectacular promposal that Andre can't refuse. But when the promposal starts to go wrong, Charlie panics and says that he couldn't possibly be Andre's secret admirer, because he's been dating Luis! Luis, however, is offended by Charlie using him as a decoy. Charlie begins to realize how much fun he's been having with Luis and thinks maybe he's been going after the wrong guy. He apologizes to Luis and asks him to be his prom date instead. Luis accepts. Meanwhile, Andre has decided to accept Charlie's promposal. Now Charlie has two dates for prom! How will Charlie decide which guy to go with?"--